STRATEGI INOVASI E-COMMERCE DALAM MENGHADAPI GLOBALISASI ( STUDI KASUS JD.ID) - Setyo Budi; Dewi Agustini Santoso; Suharnawi Suharnawi (Jurnal Sistem Informasi dan Informatika (Simika), 2023)
Advances in information technology are one of the fundamental things in technological development that cannot be stopped, this will continue to grow to be large and can provide a large level of change in the pattern of people's lives. E-commerce can be said as the development of information technology. And one company that does this is JD.ID. JD. ID is an e-commerce company that has the positioning of "original goods" offered to consumers. This is JD.ID's biggest strength and has an e-commerce strategy that really attracts consumers' attention. The data collection method used in this study is a survey, where the problem discussed is how the phase of change and innovation can be implemented at JD.ID. The method used to analyze is McKinsey 7S. The results that will be obtained from this journal are phases of change that may and/or can be recommended to JD.ID, as a recommendation and/or input so that JD.ID can develop into an even bigger e-commerce company and JD.ID can become the broader e-commerce market leader. Changes must always be made to be able to adapt to the needs required by society and on the one hand is flexibility in dealing with this.